The Influence of Corporate Social Responsibility (CSR) and Company Size on Financial Performance in Manufacturing Companies Listed on the IDX in 2021-2023 - Az Zahara, Fatimah; Darmawati; Febriyanti, Ekea Multi (Journal of Economics and Management Technologies, 2025)
The Objectives – to find out and analyze the Influence of Corporate Social Responsibility (CSR) and Company Size on Financial Performance in Manufacturing Companies Listed on the IDX in 2021-2023. The Methods/approaches – purposive sampling. Data collection techniques using secondary data. Data were obtained from 19 food and beverage sub-sector manufacturing companies for 3 years so that the sample used in this study was 57. The analysis tool used was SPSS 26 with multiple linear regression analysis method. The Results –  The results showed that corporate social responsibility (CSR) had a positive and significant effect on financial performance with a regression coefficient value of 3.372 with a t count of 2.995 and a t table of 2.004 with a significance value of 0.004 <0.05, meaning that if the Corporate Social Responsibility (CSR) variable increases, the Return On Asset (ROA) also increases. The company size variable had a negative and significant effect on financial performance with a regression coefficient value of -0.230 with a t count of -13.469 and a t table of 2.004 with a significance value of 0.000 <0.05, if the Company Size variable increased, so the Return On Asset (ROA) decreased.